2017
DOI: 10.7717/peerj.4159
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling diatom species complexes: does morphometry suffice?

Abstract: Accurate taxonomic resolution in light microscopy analyses of microalgae is essential to achieve high quality, comparable results in both floristic analyses and biomonitoring studies. A number of closely related diatom taxa have been detected to date co-occurring within benthic diatom assemblages, sharing many morphological, morphometrical and ecological characteristics. In this contribution, we analysed the hypothesis that, where a large sample size (number of individuals) is available, common morphometrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The reason for including such dataset was to perform a comparison study of the discriminant power of the feature descriptors used by (Mann et al, 2004) and ours. Dataset 3 was recently analyzed by (Blanco et al, 2017) and the reasons for its analysis were the same as the previuos case. Dataset 1 explicitly includes different stages of the life cycle of the diatoms, which increases the degree of intraclass variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for including such dataset was to perform a comparison study of the discriminant power of the feature descriptors used by (Mann et al, 2004) and ours. Dataset 3 was recently analyzed by (Blanco et al, 2017) and the reasons for its analysis were the same as the previuos case. Dataset 1 explicitly includes different stages of the life cycle of the diatoms, which increases the degree of intraclass variability.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 13 shows a perfect cluster separation. In (Blanco et al, 2017) the authors concluded that only morphometric measurements based on taxonomic keys such as the length/width ratio or the striae density are not sufficient for diatom classification when classes are similar. They obtain correct classification rates between 40% and 70% when classifying six different species of the Gomphonema genera (see Table 3) with different classifiers and clustering algorithms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The camera is connected to the computer through an USB2.0 connection, providing an image size of 2592 x 1944 pixels. Images corresponding to (Mann and Bayer, 2018;Blanco et al, 2017) in Table 1, 2 and 3 have been provided by the authors. Table 1 form the dataset used in this paper for a total of 703 images of eight different classes.…”
Section: Databasementioning
confidence: 99%
“…These shells (valves) are held together by extracellular polymeric substances (EPS) and silicate bands (copulae/girdle bands). The primary morphological parameters (valve length, valve width, and stria density) can be used in identifications, but may not be sufficient for species identifications (e.g., Blanco et al., ). The shape of the diatom typically forms a definable face and a rectangular‐like shape in side view.…”
mentioning
confidence: 99%